2023
DOI: 10.1186/s12879-023-08743-6
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection rates, change in antibody titers and adverse events after COVID-19 vaccination among patients previously infected with COVID-19 in Metro Manila, Philippines: a secondary analysis of a completed cohort study

Carol Stephanie C. Tan-Lim,
Ma. Liza Antoinette M. Gonzales,
Leonila F. Dans
et al.

Abstract: Background Variation in immune response to COVID-19 vaccines is observed among different ethnicities. We aimed to describe the reinfection rates, change in antibody titers, and adverse events among Filipinos. Methods This is a secondary analysis of a cohort study of 307 participants within one year of having COVID-19 infection. We measured COVID-19 antibody levels at pre-determined timepoints (Days 21, 90, 180, 270, and 360 from initial infection).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our results also suggested no significant difference found in reinfection rates between the CoronaVac vaccine and the BNT162b2 vaccine. However, a previous study has reported that receiving mRNA vaccines leads to a lower reinfection rate than inactivated vaccines [34],…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results also suggested no significant difference found in reinfection rates between the CoronaVac vaccine and the BNT162b2 vaccine. However, a previous study has reported that receiving mRNA vaccines leads to a lower reinfection rate than inactivated vaccines [34],…”
Section: Discussionmentioning
confidence: 97%
“…Our results also suggested no significant difference found in reinfection rates between the CoronaVac vaccine and the BNT162b2 vaccine. However, a previous study has reported that receiving mRNA vaccines leads to a lower reinfection rate than inactivated vaccines [34], while another study suggested that Combined vaccination may offer superior reinfection protection than either alone [35]. Considering the potential long-term persistence of the SARS-CoV-2 virus, individuals with relatively lower immune responses may benefit from a booster vaccination after primary infection, and further investigations were required to confirm the effects of different vaccine types.…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 becomes endemic globally and immunization protocols evolve, people experiencing numerous successive natural and/or artificial SARS-CoV-2 exposures, may undergo more extreme immune PLOS ONE responses. In response to the rapid increase in reported levels of anti-SARS-CoV-2 antibody titers, some laboratory protocols now report results up to 250,000 U/mL [16]. While a clinical antibody-based threshold of protection against COVID-19 infection has not yet been defined, serological results remain important in clinical decision-making, such as vaccination protocols for immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 99%